Beyond the school: encounters with non-forma education spaces in the teaching of Ecology (Research, Society and Development, 2023)
In this article we report the experience of using a Non-Formal Education Space (ENFE) for learning in Ecology developed with students of the 3rd Year of High School from a public school in the Municipality of Castanhal in the interior of Pará. of the action-research type, using as instruments for data production: audiovisual recordings, photographs, field observations and letter writing by the students. The objective of this study is to analyze in which terms the learning of ecological concepts occurs using a Non-Formal Education Space. During the visit to the ENFE space, students were encouraged to present their hypotheses and encouraged to discuss, observe and argue their ideas, transposing theoretical concepts into practice, favoring the passage from manipulative action to intellectual action, promoting meaningful learning through interaction of ecological concepts with the reality of students and their community. By proposing investigative activities to students at ENFE, we noticed an increase in students' interest and participation in environmental problems and reflections on the need and possibility of intervening in the observed reality.